Spiral-shaped metallic implant in the treatment of Achilles tendon ruptures: an experimental study on the Achilles tendon of sheep - (:unkn) unknown (My University, 2007)
There are 2 main factors contributing to the strength of tendon repair: the tensile strength of the material used in repair and the tendon-holding capacity of the suture configuration. In the current study, we aimed to find a technique with high repair strength by increasing both the tensile strength of the material and the tendon-holding capacity of the configuration. We developed metal implants (models 1 and 2) made from stainless-steel wire with 2 different spiral-shaped configurations. We measured tendon-holding capacities of these alternative implants biomechanically and compared them with frequently used suture techniques, the Bunnell and locking loop, which were achieved with 5 Ticron sutures. Sixty-four sheep Achilles' tendons were used in the study as 16 tendons in each group. Model 2 was more resistant to deformation under loading when compared with model 1. The results demonstrated that model 2 was superior to model 1 and both suture techniques. This study could be accepted as a step for reaching a strong tendon repair technique. It should be emphasized that the technique needs to be improved technically to make it convenient for clinical use.
Keywords: Animals; Equipment Design; Equipment Failure; Suture Techniques; Tensile Strength; Models, Animal; Achilles Tendon; Stainless Steel; Implants, Experimental; Sheep